2019
DOI: 10.3389/fphar.2019.00599
|View full text |Cite
|
Sign up to set email alerts
|

Deacylcynaropicrin Inhibits RANKL-Induced Osteoclastogenesis by Inhibiting NF-κB and MAPK and Promoting M2 Polarization of Macrophages

Abstract: Inflammation can promote the maturity of osteoclasts and bone resorption in many bone disease such as osteoporosis and arthritis. Here, we aimed to investigate the inhibitory effects of deacylcynaropicrin (DAC) on osteoclastogenesis and bone resorption induced by RANKL. Bone-marrow-derived macrophages were used for assessing the influence of DAC on polarization of macrophages and osteoclastogenesis in vitro . Inducible nitric oxide synthase (iNOS) and CD206, as well as osteoclastogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…8 Li et al reported that deacylcynaropicrin inhibited RANKL-mediated osteoclast fusion by promoting M2-type macrophage polarization. 24 A large number of studies have reported that M1-type macrophages were stimulated and induced by wear debris, which is generated from the surface of an implant prosthesis, and released proinflammatory cytokines, creating a proinflammatory microenvironment. 10,43,44 This proinflammatory microenvironment further activates the osteoclastic signalling pathways and promotes the recruitment and differentiation of osteoclast precursor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Li et al reported that deacylcynaropicrin inhibited RANKL-mediated osteoclast fusion by promoting M2-type macrophage polarization. 24 A large number of studies have reported that M1-type macrophages were stimulated and induced by wear debris, which is generated from the surface of an implant prosthesis, and released proinflammatory cytokines, creating a proinflammatory microenvironment. 10,43,44 This proinflammatory microenvironment further activates the osteoclastic signalling pathways and promotes the recruitment and differentiation of osteoclast precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,24 Therefore, the immunomodulatory effects of curcumin on RAW264.7 cells were investigated using flow cytometry, ELISA, and immunofluorescence staining. 8,24 Therefore, the immunomodulatory effects of curcumin on RAW264.7 cells were investigated using flow cytometry, ELISA, and immunofluorescence staining.…”
Section: Immunomodulatory Effect Of Curcumin On Macrophage Polarizamentioning
confidence: 99%
See 1 more Smart Citation
“…Many other related reports have noted that M1‐MΦ and M2‐MΦ participated in the inflammatory osteolysis 21,22 . In order to obtain M1‐MΦ, BMMs were stimulated with 50 ng/mL LPS or 20 ng/mL IFN‐γ for another 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Many other related reports have noted that M1-MΦ and M2-MΦ participated in the inflammatory osteolysis. 21,22 In order to obtain M1-MΦ, BMMs were stimulated with 50 ng/mL LPS or 20 ng/mL IFN-γ for another 24 hours. Individually, to generate M2-MΦ, the BMM cells were incubated with 20 ng/mL IL-4 or 20 ng/mL IL-13 in the presence of 30 ng/mL M-CSF for 24 hours.…”
Section: In Vitro Modulation Of Macrophage Polarization and Repolarizmentioning
confidence: 99%